BRIDGING INDIA’S EMPLOYMENT CRISIS: INTEGRATING BHARATIYA LEADERSHIP PRINCIPLES WITH MODERN STRATEGIES (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The Employment Challenge is a complex, heavy threat to economic stability, social harmony and long-term development a goal that is embedded in a perennial employment crisis. India ranks as one of the fastest-growing economies in the world, yet stagnant job growth, skills mismatches, and disguised unemployment undermine its demographic dividend. The paper discusses the contemporary job crisis in the context of Bharatiya leadership principles that draw inspiration from ancient Indian knowledge systems. Dharma (duty), Seva (service), Swadeshi (self-reliance), Lok Kalyan (public welfare) are some of our core concepts that spell out the moral, ethical, and practical principles for ethical governance, inclusive development, and sustainable employment solutions. The study making the case from historical references such as Emperor Asoka, Shivaji Maharaj, and modern leaders like Mahatma Gandhi and Jawaharlal Nehru concludes that time-tested basics can lead to economic turnaround and job creation. It calls for an integration of Bharatiya thought with contemporary economic policies on rural upliftment, local skill development and green jobs. This synthesis of timeless leadership principles with 21st-century practices provides a deep-rooted cultural solution to India's unemployment crisis and a new future which is more equitable, self-reliant, and prosperous.